(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
The element that links skeptron (“sceptre”)and rabdon (“cane”) in Greek tradition is the authority devolving to the one who holds it, as he becomes an intermediary between the human and divine worlds, the spokesperson of the divinity with the double significance of poet and judge. Sometimes episodes of myth confuse the particular elements of the two semantic areas in which the “cane” has a key role, thereby broadening the semantic scope of the scene. Two examples: the scepter instead of the lyre is given to Hesiod by the Muses (Theogony, lines 30 ff) and enables him to “eternalize the past and the future”, but also makes himself equal to the basileis, whose objectivity and judgment he challenges; the cane instead of the scepter is what Apollo gives to Hermes in exchange for the lyre (Hymn to Hermes, lines 528 ff.), so that legislative capabilities and poetic – musical competences reinforce the importance of the object precisely through their coexistence.